2019
DOI: 10.1021/acssuschemeng.9b02065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ZrB2 Formation in Al–Si Alloy and Application in Si Purification

Abstract: The formation of ZrB2 particles in Al–Si alloys not only improves the properties of the Al–Si alloy but also helps remove B from Si for the preparation of solar-grade Si. A thermodynamic study was performed to identify the mechanism of ZrB2 formation in Al–Si alloys. The precipitated B-bearing particles, i.e., ZrB x , were determined to be ZrB2 via electron probe microanalysis. The composition of the Al–Si alloy, which could form stable ZrB2 particles, was determined by measuring and calculating the equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…However, 68% of Si feedstock is lost in various forms of Si-containing waste during the PV production chain, where more than 40% of high-purity Si is wasted by slicing of wafers using a wire sawing process . The recycling of the Si kerf loss is considered as a cost-effective and circular-economy solution for an advanced low-cost Si-based PV, which has received plenty of attention. , Although the kerf loss of Si particles remains in high purity, it is noteworthy that the boron (B) and phosphorus (P) content in Si particles increases significantly [about dozens to hundreds of parts per million (ppm)] because of the contamination of electroplating solution containing pyrophosphate on the diamond wire saw, which limits the use of recycled Si powder as Si feedstock. , Briefly, B and P are removed step by step through the form of oxidizing slag for removing B and vacuum evaporation for removing P, which is of low-efficiency and high-energy consumption …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 68% of Si feedstock is lost in various forms of Si-containing waste during the PV production chain, where more than 40% of high-purity Si is wasted by slicing of wafers using a wire sawing process . The recycling of the Si kerf loss is considered as a cost-effective and circular-economy solution for an advanced low-cost Si-based PV, which has received plenty of attention. , Although the kerf loss of Si particles remains in high purity, it is noteworthy that the boron (B) and phosphorus (P) content in Si particles increases significantly [about dozens to hundreds of parts per million (ppm)] because of the contamination of electroplating solution containing pyrophosphate on the diamond wire saw, which limits the use of recycled Si powder as Si feedstock. , Briefly, B and P are removed step by step through the form of oxidizing slag for removing B and vacuum evaporation for removing P, which is of low-efficiency and high-energy consumption …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Briefly, B and P are removed step by step through the form of oxidizing slag for removing B and vacuum evaporation for removing P, which is of low-efficiency and high-energy consumption. 12 Oxidizing slag treatment has been considered as an ideal way to remove B and P through the oxidation reaction at the slag/ metal interface. 13 B and P were oxidized at the interface by the eqs 1 and 2 and then entered into the slag.…”
Section: Introductionmentioning
confidence: 99%
“…The process of Si purification is accompanied by the migration of impurity elements and the transformation of impurity phases. Chemical reconstruction can change the morphology and location of impurities, such as the transformation from elemental elements to compounds and the transformation from the solid solution of the matrix to precipitated phases at grain boundaries or phase boundaries. , The essence of the alloy refining method of Si is to use the principle of chemical reconstruction to realize the selective modification and denaturing of metallic and nonmetallic impurities in Si, which can weaken the combination between impurities and the Si matrix and enhance the removal of impurities at the interface . Its connotation mainly includes two aspects: one is the alloy refining process using a large number of metal liquidating agents; the other is the process of impurity modification by adding a small amount of impurity modifier on the basis of the molten refining system. ,, Metal liquidating agents and modifiers are collectively referred to as impurity chemical reconstruction medium, which are mainly transition metals such as Cu, Fe, Sn, Ti, and the main group metals such as Al and Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical reconstruction can change the morphology and location of impurities, such as the transformation from elemental elements to compounds and the transformation from the solid solution of the matrix to precipitated phases at grain boundaries or phase boundaries. , The essence of the alloy refining method of Si is to use the principle of chemical reconstruction to realize the selective modification and denaturing of metallic and nonmetallic impurities in Si, which can weaken the combination between impurities and the Si matrix and enhance the removal of impurities at the interface . Its connotation mainly includes two aspects: one is the alloy refining process using a large number of metal liquidating agents; the other is the process of impurity modification by adding a small amount of impurity modifier on the basis of the molten refining system. ,, Metal liquidating agents and modifiers are collectively referred to as impurity chemical reconstruction medium, which are mainly transition metals such as Cu, Fe, Sn, Ti, and the main group metals such as Al and Zn. The common characteristics of these metal elements are that they have a very small separation coefficient (10 –4 –10 –8 ) in Si, which is conducive to the efficient separation of the medium. , The second of these metal elements in the electron configuration are more easy to lose one electron to form a variable valence state and has not filled the valence shell d orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it has been theoretically and experimentally confirmed that P tends to segregate along Si grain boundaries, its segregation coefficient ( k p = 0.35) is still relatively high compared to metallic impurities, which is usually less than 10 –3 . To further improve the extraction efficiency of P and other impurities, considerable attention has been paid to redistribute impurities by adding alloying elements as impurity getters such as calcium (Ca), magnesium (Mg), titanium (Ti), aluminum (Al), copper (Cu), tin (Sn), , iron (Fe), and nickel (Ni) . The widely known solvent refining usually involves alloying by Al, Sn, Cu, and Fe with a large amount of metal addition (around or more than 50 wt %).…”
Section: Introductionmentioning
confidence: 99%